An uncle's guide to GST : the goods & services tax laid bare - Choong, Kwai Fatt , 1965- (Infoworld, 2014)
An uncle's guide to GST aims to unlock the complexity of the Malaysia's GST model. It explains, with illustrations,the various concepts and mechanism involved, in a simple manner for the easy comprehension of the man in the street.